Integralidade da atenção na assistência hospitalar: um estudo com profissionais que participam do atendimento ao usuário - Genilton Rodrigues Cunha (2007)
This is a qualitative case study based on comprehensive sociology, which had the objective of understanding the concept of integrality of attention by health workers who work in the direct care for patients in an emergency ward of a public hospital in Belo Horizonte, Minas Gerais. The emergency ward of the João XXIII Emergency Hospital was chosen. It is a public unit of the Single Health System linked to the State Health Secretariat and belonging to the Hospital Foundation of the State of Minas Gerais. Fifteen workers of different categories were interviewed, including two welfare workers, two nurses, two nursing auxiliaries, one nursing technician, two physical therapists, one speech therapist, two physicians, one nutritionist and two psychologists. The data was collected from August to November 2006, through documents from the institution, interviews with a semi-structured questionnaire with research subjects and direct observation of the daily work of health workers. The data were treated and analyzed by the content analysis method. From the data arose four empirical categories: 1. Integrality: a routine construct, subdivided into four subcategories: Notions of integrality; The integral care; The humanization of assistance; The bond: an issue that goes beyond the walls of the institution; 2. The health worker in the face of the suffering of the patient; 3. Intersectoriality: to rethink the net of care, subdivided into: Intersectoriality in the hospital: a space permeated by rivalries; Intersectoriality in the health system); 4. Team work in health care. It was seen that the health professionals act in the daily one of a soon-aid hospital of form broken up, where each one has their own idea about integrality of the attention and does it according to his/her own judgment. Therefore it is necessary to build intersectoriality in all the places in which it is inserted, in so far as there are discussions on integrality, that is, it is to dive into the discussion on this so as to build a practice that is in construction in their daily routine. This study is meant to, therefore, contribute to a better understanding of the concept of integrality by health workers in the emergency wards, and consequently, the perceptions and practices based on them. It is hoped that this will bring about further research on the theme, as well as to bring some reflection by health managers on integrality of care at the tertiary care level and by health care workers in their daily practice.